Performing a political shift: avant-garde music in Cold War Spain - Sacau-Ferreira, E (2011)
In my thesis, Performing a Political Shift: Avant-Garde Music in Cold War Spain, I argue that towards the end of the 1950s the Spanish ultra-conservative regime of Francisco Franco started to promote avant-garde music. This music contrasted with the aesthetically conservative one that had been promoted since the end of the Civil War (1936-1939). I examine the causes of this shift and reveal for the first time that they are connected to specific trends in Spanish politics and policies. In terms of national politics, the second phase of the Spanish dictatorship, from the late 1950s until Franco’s death in 1975, was dominated by young ministers who wanted to distance themselves from previous cabinets, mostly controlled by ultra-nationalist fascist politicians. These younger politicians styled themselves as part of a ‘technocratic’ regime. Thanks to its supposed ‘objectivity’ and ‘purely musical’ ideology-free concerns, avant-garde music sat well with these technocrats’ views of modern Spain, that is, a country benefitting from ‘objective’, ideology-free progress. On an international level, the defeat in the 1940s of Mussolini and Hitler, Franco’s main allies, had resulted in isolation for Spain. In order to break this isolation, the Spanish regime started to make a sustained effort at the end of the 1950s to establish diplomatic relations with other Western countries. These relations resulted in cultural, economic and military agreements with European democracies and the US. I also consider why recent Spanish musicology has failed to confront the political implications of the promotion of avant-garde music under Franco. I connect this void with the Spanish transition to democracy (1975-1978), which recent historians have called an exercise in amnesia, a discourse of forgiveness meant to promote reconciliation between Spaniards. As a result of this transition, the political implications of the activities of the composers and musicologists during the Franco years have been ignored or forgotten. The results of my thesis challenge the widely accepted view of the European avant-garde as a left-leaning movement. The main contribution of my thesis is precisely its substantial consideration of the cultural and political meanings of the avant garde and its context, using Franco’s Spain as a case in point.